Seismic Risk Assessment of Optimally Designed Highway Bridge Isolated by Ordinary Unbounded Elastomeric Bearings - Ali Maghsoudi-Barmi; Ali Khansefid; Alireza Khaloo; Milad Ehteshami Moeini (Numerical Methods in Civil Engineering)
Recent experimental research has shown that ordinary unbounded steel reinforced elastomeric bearings (SREBs) can be considered as an attractive cost-effective option for the seismic isolation of highway bridges. To further investigate its benefits, the current study is focused on the seismic risk assessment of an optimally designed highway bridge isolated by SREB system. A typical three-span highway bridge located in Tehran Metropolis is considered and designed with the SREBs as isolation system, applying a multi-objective optimization procedure to reduce both the seismic isolation deformation and the base shear, simultaneously. Then, the vulnerability of the bridge is evaluated through an Incremental Dynamic Analysis (IDA) using a suite of 20 ground motion records, and the fragility functions are generated. Next, for the hazard modelling, all active faults around the site of the project are taken into account to simulate the earthquake scenario. Afterwards, probable earthquake scenarios during the design life of the bridge are generated randomly, including the events, as well as their corresponding synthetic stochastic accelerograms. In the last step, the response of the bridge and its losses are calculated under the entire scenarios. Finally, the seismic risk of the bridge is estimated. The results indicate an improved behavior of the bridge, and the capability of isolation system in mitigating the earthquake excitation. Moreover, the results, obtained from the assessed seismic risk, show a significant reduction in the amount of bridge losses.